An Improved Calibration Method for the Misalignment Error of a Triaxial Magnetometer and Inertial Navigation System in a Three-Component Magnetic Survey System - Supeng Li; Defu Cheng; Quanming Gao; Yi Wang; Liangguang Yue; Mingchao Wang; Jing Zhao (Applied Sciences, 2020)
In order to calibrate the misalignment error of a triaxial magnetometer and an inertial navigation system in a three-component magnetic survey system, an improved method with easy realization is proposed in this paper. We establish the misalignment error model based on Euler’s theorem. We transform the calibration of misalignment error into estimating calibration parameters to minimize the value of objective function. Then, the nonlinear least squares method is used to estimate the calibration parameters. In the simulation experiment, the deviation between the value and the preset value is within 1 nT. In the field experiment, the fluctuation value of the x, y, and z components reduce to 1.09%, 0.92%, and 1.28%, respectively. The absolute deviation values are reduced to 0.72%, 0.70%, and 0.81% and the standard deviation value are reduced to 0.74%, 0.71%, 0.86%, respectively. The proposed method has advantages of high operability and precision as compared with existing methods.